Supporting lower-income working women to initiate breastfeeding: Learning who is breastfeeding and what helps. Issue 9 (September 2018) - Middlemiss, Wendy; Glaman, Ryan; Seddio, Kaylee; Suerken, Cynthia K.; Reboussin, Beth A.; Daniel, Stephanie S.; Payne, Chris C.; Leerkes, Esther; Grzywacz, Joseph G.
ABSTRACT: Background and purpose: Based on the Women, Work, and Wee Ones longitudinal study, mothers' likelihood of breastfeeding is examined across demographic and health variables. Methods: Frequencies of breastfeeding and cosleeping by 285 mothers from the Women, Work, and Wee Ones cohort are reported as related to mothers' work schedule, marital status, or mother or infant health. Conclusions: Breastfeeding rates were about 30% across most maternal characteristics. The frequency of mothers' breastfeeding was higher when mothers were both breastfeeding and cosleeping (breastfeeding-cosleeping), in comparison with breastfeeding only, as evident for mothers with nonstandard work schedules. Cosleeping was common across all mothers. Breastfeeding rates were low, perhaps reflecting challenges of early care. Premature infants were more likely to be cosleeping than breastfeeding. Approximately 30% of mothers breastfed across the different factors examined. Implications for practice: The information may help nurse practitioners in addressing early care needs and supporting breastfeeding across groups. Younger mothers were least likely to breastfeed and reported higher frequency of cosleeping. Overall breastfeeding frequency was higher when mothers were cosleeping. Nurse practitioners may find it important to provide clear information about safe infant sleep and safe approaches to protecting infants.